Rights talk in a genocide: Myanmar as a lens for the problem of rights in Buddhist political thought - Sukala, Cory (Politics, religion & ideology, 2023)
With their integration into the global political world, the historically Buddhist countries of Southeast Asia have begun to augment, sometimes to the point of replacement, their traditional political structures with Westernized political institutions. Despite these formal changes, far less development has been made as a matter of underlying political theory. Though the language of contemporary Buddhist political thought and action is colored with talk of rights, it remains unclear how firmly this new orientation is founded. The consequences of this mixture of Western democratic political forms built upon an underlying foundation of Buddhist political theory can be seen in the developing human rights crisis in Myanmar. On the subject of the Muslim Rohingya, advocates of Burmese democracy, such as Aung San Suu Kyi, have seemingly found common cause with the military junta, with the country’s newly-minted democratic institutions proving themselves to be inadequate as a means of sustaining rights protections for the religious minority group. This paper examines the standing of rights-language in Buddhist political thought and how these concepts have thus far proven insufficient as a surrogate to similar conceptions in the liberal tradition as a foundation for political protections.